2020
DOI: 10.4067/s0718-58392020000200234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a homofermentative lactic acid bacteria additive on the quality of sugar-beet pulp silage and animal response of dairy cows with restricted access to pasture

Abstract: Sugar-beet (Beta vulgaris L. subsp. vulgaris) pulp is a valuable by-product from the manufacture of beet sugar fresh which is normally preserved in the form of silage. The aim of the present research was to evaluate the effect of adding a homofermentative lactic acid bacteria silage additive during the ensiling period on fermentation and quality of sugar-beet (SB) pulp silage and the animal performance of dairy cows given restricted daily access to pasture. Twelve Holstein × Friesian crossbred cows were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In contrast, Li et al [72] treated corn steep liquor silage with LAB and reported improved DM digestibility, which resulted in less methane production compared to untreated silage. Further, a study by Pulido et al [90] showed an improvement in the nutritive value of sugar beef pulp silage with LAB inoculation, which increased milk production from dairy cows by 2%, though milk composition was not affected by the inoculation.…”
Section: Animal Performancementioning
confidence: 99%
“…In contrast, Li et al [72] treated corn steep liquor silage with LAB and reported improved DM digestibility, which resulted in less methane production compared to untreated silage. Further, a study by Pulido et al [90] showed an improvement in the nutritive value of sugar beef pulp silage with LAB inoculation, which increased milk production from dairy cows by 2%, though milk composition was not affected by the inoculation.…”
Section: Animal Performancementioning
confidence: 99%
“…Gram-positive bacteria in the rumen have low molecular weight, so they are prone to the action of tannins, and are consequently inhibited (Benchaar and Greathead, 2011;Patra and Saxena, 2011;Francisco et al, 2015;Morales and Ungerfeld, 2015;Thao et al, 2015). Pulido et al (2020) reported that the addition of lactic acid bacteria as additive increased the metabolizable energy content of the silage and reduced its butyrate concentration.…”
Section: Rainy Seasonmentioning
confidence: 99%
“…There are studies that have evaluated the inclusion of fresh or ensiled sugar beets [ 20 , 21 , 22 , 23 ] and fodder beets [ 24 , 25 , 26 , 27 ] in dairy cow diets. Few studies have involved the feeding of high concentrations of sugar from beets to replace starch in the diet.…”
Section: Introductionmentioning
confidence: 99%